Task-Based Learning in Academic Writing for EFL Students at Sabratah University (Comprehensive Journal of Science, 2025)
This qualitative study explores the use of Task-Based Learning (TBL) in teaching academic writing to EFL students at Sabratah University. Based on classroom observations, student feedback, and literature review, the research found that authentic, communicative writing tasks increased learner autonomy, engagement, and confidence. Collaborative projects, such as research proposals and reports, improved fluency, organization, and vocabulary through peer feedback. Students viewed TBL positively, citing deeper understanding of writing processes and less fear of errors. Despite challenges like preparation time and initial resistance to group work, TBL effectively promoted independent learning and practical language use in Libyan EFL classrooms.